2012
DOI: 10.1152/ajpgi.00178.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 inhibits gastric acid secretion via a central vagal mechanism in rats

Abstract: MW. Nesfatin-1 inhibits gastric acid secretion via a central vagal mechanism in rats. Am J Physiol Gastrointest Liver Physiol 303: G570 -G577, 2012. First published June 21, 2012; doi:10.1152/ajpgi.00178.2012.-Nesfatin-1, a novel hypothalamic peptide, inhibits nocturnal feeding behavior and gastrointestinal motility in rodents. The effects of nesfatin-1 on gastrointestinal secretory function, including gastric acid production, have not been evaluated. Nesfatin-1 was injected into the fourth intracerebral ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
(51 reference statements)
1
29
0
1
Order By: Relevance
“…Particularly, a central injection of an anorexigenic dose of nesfatin-1 is also capable to inhibit the 2-deoxy-d-glucose-stimulated gastric acid secretion via vagal efferents in rats, as suggested by a 16-fold increase of c-fos-positive neurons in the DMNX, but not in the NTS (Xia et al 2012). In agreement, 80% of DMNX neurons projecting to the stomach are nesfatin-1 positive (as was shown by retrograde tracing) (Bonnet et al 2013).…”
Section: Gastric Distension and Gastric Acid Secretionsupporting
confidence: 71%
“…Particularly, a central injection of an anorexigenic dose of nesfatin-1 is also capable to inhibit the 2-deoxy-d-glucose-stimulated gastric acid secretion via vagal efferents in rats, as suggested by a 16-fold increase of c-fos-positive neurons in the DMNX, but not in the NTS (Xia et al 2012). In agreement, 80% of DMNX neurons projecting to the stomach are nesfatin-1 positive (as was shown by retrograde tracing) (Bonnet et al 2013).…”
Section: Gastric Distension and Gastric Acid Secretionsupporting
confidence: 71%
“…Gastric NUCB2/ nesfatin-1 mRNA expression levels were higher than expression levels in other peripheral organs and brain (48). Nesfatin-1 reduced the release of gastric acid in a dose-dependent manner and influenced gastrointestinal motility (2,24,55,58). Its presence in pancreatic cells was detected particularly in the beta cells of Langerhans islets (15,27).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 97%
“…Existing evidence using Ca 2+ flux as an index suggested that NUCB2/nesfatin-1’s action in neurons is mediated by a Gi/o-protein-coupled receptor as the response is abolished by pertussis toxin [7, 14]. In particular, in vitro studies showed that nesfatin-1 stimulates Ca 2+ influx into neurons of the rat hypothalamus [7, 15], rat dorsal motor nucleus of the vagus nerve (DMV) [16], and mouse vagal afferent nodose ganglion [17]. Results obtained using inhibitors specific for subtypes of Ca 2+ channels indicate that the nesfatin-1-induced elevation of [Ca 2+ ] i exhibits pharmacological characteristics of either N-, L-, and/or P/Q channels.…”
Section: Introductionmentioning
confidence: 99%